PROSES PENYERAPAN KATA BAHASA INGGRIS KE DALAM BAHASA JEPANG: (KAJIAN FONOLOGI GENERATIF TRANSFORMASIONAL) - Muslihah, Muslihah (IZUMI, 2018)
(Title: The Analysis of Loan Words of English Language Transformed into Japanese Language (Study of Generative Transformational Phonological) The aims of this research are to explain the phonological processes and phonological rule in loan words of English language into Japanese language through generative phonological studies. This research used qualitative descriptive method. The research data are taken from Japanese dictionary loan words. The result shows eight phonological processes and phonological rules in the process of transformation English language to Japanese. (1) the process of adding segment /u/ at the end of the words (2) segment additions /o/ at the end of the words (3) segment additions /u/ in the middle of words  (4) segment additions /o/ in the middle of words (5) substitution of phoneme /l/ to /r/, (6) substitution of phoneme /v/ to /b/, (7) segment additions /i/, (8) substitution of phoneme /t/ to /c/. The transformation of phonological processes on the loan words of English language into Japanese language affected by the internal factor. gb777gb777slot gacorgb777gb777GB777GB777slot gacorslot gacor